Meconium Peritonitis In Utero-the Value of Prenatal Diagnosis in Determining Neonatal Outcome - Chao-Nin Wang; Shuenn-Dyh Chang; An-Shine Chao; Tzu-Hao Wang; Ling-Hong Tseng; Yao-Lung Chang (Elsevier, 2008)
Objective: Meconium peritonitis (MP) is a chemical peritonitis caused by fetal intestinal perforation in utero. Its incidence is rare, but serious neonatal morbidity or even mortality can occur if the diagnosis is not made until after birth. Prenatal diagnosis is important in prompting early postnatal surgical intervention, and so improving neonatal outcome. Materials and Methods: Fourteen cases diagnosed in utero with MP from January 1996 to December 2005 were enrolled in this study. The final diagnoses were established by surgical findings or postnatal radiography. The prenatal ultrasound features, neonatal birth characteristics, surgical findings, postnatal management and neonatal outcomes were reviewed. Results: All infants received follow-up care at our hospital. Prenatal ultrasound findings included fetal ascites (100%), intra-abdominal calcification (93%), dilated bowel loops (57%), pseudocysts (29%), and polyhydramnios (50%). Four infants (4/14; 28.5%) did not undergo postnatal surgery, but survived well. The mean gestational age at detection was significantly earlier in the non-surgery group (23 ± 3.6 weeks) than in the surgery group (31.7 ± 2.5 weeks). One infant (7.1%) died because of sepsis after two neonatal operations. The overall survival rate was 92.9%. Conclusion: MP can be diagnosed by prenatal ultrasound, and the neonatal outcome is favorable. Early detection is not associated with poor neonatal outcome, and selective termination is unnecessary. Resolution of dilated bowel loops and polyhydramnios predict a low rate of postnatal surgical intervention.